2023
DOI: 10.3390/su151411180
|View full text |Cite
|
Sign up to set email alerts
|

Using Kano Model to Understand an Effect of Specialization and Perceived Risk on Demand for Services in Marine Tourism

Abstract: This paper attempted to combine the Kano model and the service blueprint for quality management in marine tourism services. It also investigated the influence of customer characteristics, focusing on services that customers directly experience. Data were collected from those who experienced marine leisure in Korea in the past three years, and an analysis of differences between groups was conducted. The difference analysis showed significant differences in the frequency of service quality factors for men and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(90 reference statements)
0
0
0
Order By: Relevance
“…Therefore, the equipment and facilities in the unique environment of the island will age in advance compared with a normal environment, and there are more security risks [57]. When Kwon and Lim used the Kano model to explore the impact of demand for marine tourism services, they found that the most critical service was project safety [58]. Therefore, it can be seen from the analysis results of this study that basic support and safety support facilities are divided into Must-be quality elements, which play a key role in the service quality of recreational fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the equipment and facilities in the unique environment of the island will age in advance compared with a normal environment, and there are more security risks [57]. When Kwon and Lim used the Kano model to explore the impact of demand for marine tourism services, they found that the most critical service was project safety [58]. Therefore, it can be seen from the analysis results of this study that basic support and safety support facilities are divided into Must-be quality elements, which play a key role in the service quality of recreational fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Kwon and Lim. or Medzík et al [62,63], when determining the quality characteristics, the quality level is determined by the highest frequency value. Therefore, even with the same quality factor, there is a limit to representing the difference between the relatively high-quality-level element and the low-quality-level element numerically.…”
Section: Study Limitations and Recommendations For Future Workmentioning
confidence: 99%